2018
DOI: 10.2134/jeq2018.02.0068
|View full text |Cite
|
Sign up to set email alerts
|

Speciation of Phosphorus from Agricultural Muck Soils to Stream and Lake Sediments

Abstract: The nature and management of agricultural soils can influence the forms of legacy P present in affected sediments; however, few studies have specifically characterized P in sediments affected by polder agriculture. In this study, the speciation of P as it flows from the muck soils of the Holland Marsh to the sediments of the West Holland River and Lake Simcoe, Ontario, Canada, was investigated. The distribution of P fractions and the characterization of organic P were analyzed by the sequential fractionation m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 71 publications
1
9
0
Order By: Relevance
“…The observed TP content (g/kg DW) in this study (0.073–2.00) was within previously reported ranges for both lake sediment (0.66–8.5 g/kg DW; Boström et al, 1988; Rydin, 2000; Søndergaard et al, 1996; Zhang et al, 2013) and streambed sediment (0.155–2.00 g/kg DW, Audette et al, 2018; Dorioz et al, 1998; Noll et al, 2009; Palmer‐Felgate et al, 2009; SanClements et al, 2009). Most of the variation in TP content was between sites, with no clear separation between streams and lakes.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The observed TP content (g/kg DW) in this study (0.073–2.00) was within previously reported ranges for both lake sediment (0.66–8.5 g/kg DW; Boström et al, 1988; Rydin, 2000; Søndergaard et al, 1996; Zhang et al, 2013) and streambed sediment (0.155–2.00 g/kg DW, Audette et al, 2018; Dorioz et al, 1998; Noll et al, 2009; Palmer‐Felgate et al, 2009; SanClements et al, 2009). Most of the variation in TP content was between sites, with no clear separation between streams and lakes.…”
Section: Discussionsupporting
confidence: 91%
“…Sequential extraction has been widely used to identify P fractions, and their potential mobility, in lake sediments (Boström et al, 1988; Rydin, 2000; Søndergaard et al, 1996; Zhang et al, 2013). In a few cases, sequential extraction has also been used for streambed sediment (Audette et al, 2018; Noll et al, 2009; SanClements et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…We found significant quantities of P in the sediments of stormwater ponds, which has also been reported in urban ponds in Minnesota, USA (Olsen, ). In our study region, a large fraction of P in the sediments of nearby wetlands and streams was also found as organic P (Audette et al, ). We found that much of this organic P was mobile and released from sediment regardless of water column oxygenation.…”
Section: Discussionmentioning
confidence: 53%
“…Three source materials were investigated; (1) turkey litter compost (TLC), (2) an agricultural organic soil (AOS) from Holland Marsh, Bradford Ontario, Canada (Terric Humisol, Canadian System of Soil Classification), and (3) a riparian soil (RS) from the rare Charitable Research Reserve site in Cambridge, Ontario, Canada (Gray Brown Luvisol, Canadian System of Soil Classification). The detailed characteristics of the TLC and AOS samples were previously reported by Audette et al (2015) and Audette et al (2018), respectively. A first chemical survey of the RS sample was performed with a tabletop scanning electron microscope (HITACHI TM3000) equipped with an energy dispersive x‐ray spectrometer (Bruker).…”
Section: Methodsmentioning
confidence: 80%